Radio-morphometric Analysis of Sella Turcica in the South Indian Population: A Digital Cephalometric Study - Ch. Sai Kiran; P. Ramaswamy; Santosh N; B. Smitha; Satish A (Arab Journal of Forensic Sciences & Forensic Medicine, 2017)
Aim: The present study was undertaken to identify the role of radio-morphometric analysis of sella turcica in sex determination. Material and Methods: A total of 260 good quality lateral cephalograms (130 males and 130 females) were randomly selected from the orthodontic database between2014 and 2015. Radiographic measurements (antero-posterior diameter and depth of sella) were carried out by a senior oral radiologist. The values obtained were tabulated in a spreadsheet and subjected to statistical analysis (SPSS version 16.0SPSS.inc Chicago 1989 – 2 “007). Results: A higher percentage of both males (70.0%) and females (67.7%) were presented with normal sella. The second best sella presentation was the shallow sella in males (16.2%). The mean antero-posterior diameter was significantly higher in females (12.25 mm) than males (11.74 mm). The mean depth of sella turcica was greater in females (8.08 mm) than males (7.68mm). Discriminant function analysis was done with gender as a grouping variable and antero-posterior dimensions and sella depth as independent variables. The formula obtained was D = 0.452 (x) +0.295(y)-7.753. (Where “D” is the discriminant score “x” is antero-posterior diameter of sella “y” is sella depth).The present study revealed an overall accuracy rate of58.1% in identifying correct gender using sella measurements. Conclusion: The present study was the first of its kind in the South Indian population and has presented results that justify the use of sella turcica for sex determination.